Patterns of Using Collections of Periodic Issues by Students at UPT Medan State University Library (International Journal of Cultural and Social Science, 2022)
Electronic Journal is a term used to describe scientific papers published in digital form that can be accessed using the internet. This study aims to determine the pattern of utilization and inhibiting factors in utilizing the printed and electronic journals of Cambridge and Emerald by users at the UPT Library of the State University of Medan. This type of research is qualitative with a descriptive approach. Data collection techniques used were interviews, observation and documentation, then data analysis techniques used three stages, namely, data reduction, data presentation and conclusion drawing. This research was conducted at the UPT Library of the State University of Medan. The results of this study indicate that in the use of printed and electronic journals, Cambridge and Emerald have been used by users in their daily needs to serve as references in fulfilling lecture assignments, research reports, and seeking the latest information. There are several obstacles faced in utilizing the printed and electronic journals of Cambridge and Emerald such as the internet network, accuracy in determining the subject, electronic journals that were found to be unsubscribed and in English.